Karakteristik Pelet Kayu Laban (Vitex Pubescens) Sebagai Bahan Bakar Alternatif Terbarukan - Alpian, Alpian; Rivaldi; Wahyu Supriyati; Luhan, Gimson; Surasana, I Nyoman (BRIN Publishing, 2023)
Fuel oil and gas in the coming years will still be the main energy source in supporting community activities. However, the increase in world oil prices led to an increase in fuel prices including gas and kerosene. One of the alternative energy sources that can be used is the use of wood waste as fuel for households or industries in the form of biomass pellets (pellets). The purpose of this study was to determine the quality of wood pellets from laban wood (Vitex pubescens) based on SNI 8021: 2014. This study used laban wood powder from the stems, branches and twigs, and tapioca flour as adhesives. The size of the powder used was 40 mesh stuck in 60 mesh. The pellet stamping used a pressure of 60 kg/cm3. The wood pellets tested included moisture content, density, volatile matter content, fixed carbon content, ash content, and calorific value. The test results showed that the stems of laban wood pellets produced better qualities than the branches and twigs parts although they were not significantly different. The range of laban wood pellets from the middle stems, branches and twigs were 11.27 ̶ 11.62% (moisture content), density were 0.34 ̶ 0.53 g/cm3, ash content were 0.83 ̶ 1,05%, volatile matter content were 71.20-72.00%, carbon content were 14.93-16.38%, and calorific value were 4486.46 ̶ 4514.46 cal/g. The test results were within the requirement of the Standards of Indonesia (SNI 8021-2014), the Korea Standard (KFS), and the Jeman Standard (DIN51371), except the density was not within the requirement of the SNI 8021-2014 Standard and the Jerman Standard (DIN51371). The density of the stem section was within the requirement of the Korean standard.